2010
DOI: 10.1021/es902256m
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Use of Performance Reference Compounds in an Oasis-HLB Adsorbent Based Passive Sampler for Improving Water Concentration Estimates of Polar Herbicides in Freshwater

Abstract: Passive samplers such as the Polar Organic Chemical Integrative Sampler (POCIS) are useful tools for monitoring trace levels of polar organic chemicals in aquatic environments. The use of performance reference compounds (PRC) spiked into the POCIS adsorbent for in situ calibration may improve the semiquantitative nature of water concentration estimates based on this type of sampler. In this work, deuterium labeled atrazine-desisopropyl (DIA-d5) was chosen as PRC because of its relatively high fugacity from Oas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 30 publications
3
105
0
Order By: Relevance
“…For sampling of polar pesticides the adsorbent was spiked with app. 4 µg/g of D 5 -desisopropylatrazine (D 5 -DIA) according to the procedure described by Mazzella et al [17] before sampler assembly and deployment. Mazzella et al [17] suggested applicability of D 5 -DIA as a suitable PRC for compensation of effects of environmental conditions (especially flow velocity) on performance of the applied variant of POCIS.…”
Section: Sampler For Polar Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…For sampling of polar pesticides the adsorbent was spiked with app. 4 µg/g of D 5 -desisopropylatrazine (D 5 -DIA) according to the procedure described by Mazzella et al [17] before sampler assembly and deployment. Mazzella et al [17] suggested applicability of D 5 -DIA as a suitable PRC for compensation of effects of environmental conditions (especially flow velocity) on performance of the applied variant of POCIS.…”
Section: Sampler For Polar Compoundsmentioning
confidence: 99%
“…4 µg/g of D 5 -desisopropylatrazine (D 5 -DIA) according to the procedure described by Mazzella et al [17] before sampler assembly and deployment. Mazzella et al [17] suggested applicability of D 5 -DIA as a suitable PRC for compensation of effects of environmental conditions (especially flow velocity) on performance of the applied variant of POCIS. Following exposure at the organising laboratory, the adsorbent material from each sampler was transferred into a pre-weighted empty solid phase extraction (SPE) cartridge, dried and the sorbent mass was recorded.…”
Section: Sampler For Polar Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the desorption process is important when considering the behaviour of a sampler after a peak concentration event [15]. Understanding the desorption process is also important when considering the use of performance reference compounds (PRCs) in passive samplers [16]. PRCs are usually isotope-labelled compounds that are pre-loaded into the sampler.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a performance reference standard (PRC), which can eliminate the influence of environmental factors (already established for hydrophobic samplers), is still limited for hydrophilic compounds. Since Mazzella et al (2010) proposed deuterated deisopropyl-atrazine-d5 (DIA d5) as an appropriate PRC for polar herbicide sampling, other compounds have been tested Miege et al 2012;Vallejo et al 2013;Belles et al 2014). Several deuterated hormones and β-blockers are also suggested by Jacquet et al 2012.…”
Section: Calibration Sampling Rates and Performance Of A Reference Smentioning
confidence: 99%